Outcomes of Meningomyelocele Repair with or without Platelet Rich Plasma Application - Haq, Mahwish Noor ul; Naumeri, Fatima; Munir, Asad; Rafiq, Hafiza Mariam; Aman, Nadir; Zafar, Zuha (Indus Journal of Bioscience Research, 2025)
Objective: Meningomyelocele (MMC) is a common congenital neural tube defect requiring early surgery and a multidisciplinary approach. This study aimed to minimize cerebrospinal (CSF) leakage and accelerate healing in infants undergoing corrective surgery. Methodology: The study consisted of 70 infants with meningomyelocele divided into two groups. The PRP group received platelet rich plasma during surgery, while the control group did not. Within the PRP group, 35 infants underwent primary defect repair. In the control group, 32 had primary repair and 3 had flap closure. Results: The results demonstrated significant benefits of PRP treatment. In the PRP group, 5.7 %( 2 infants) experienced CSF leakage and 8.6% (3 infants) developed meningitis. Additionally, 17.1%(6 infants) had local skin infections and none had wound dehiscence. In contrast, the control group had substantially higher complications rates: 17.1%(6 infants) CSF leakage, 22.9%( 8 infants) meningitis, 45.7%(16) local skin infection and 12.9%(9 infants) wound dehiscence. Conclusion: This study concludes that PRP treatment significantly reduces CSF leakage, skin necrosis, meningitis and wound dehiscence in postoperative meningomyelocele infants. PRP enhances wound healing and minimizes complications, potentially reducing morbidity and mortality. These findings suggest PRP therapy as a valuable adjunct to meningomyelocele surgery.